2020
DOI: 10.30773/pi.2019.0278
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Influence the Overlap Syndrome in Functional Gastrointestinal Disorder and Quality of Life among Psychiatric Patients in South Korea

Abstract: Objective The aim of this study was to investigate the predictor variables that could influence overlap syndrome in functional gastrointestinal disorders (FGID) among psychiatric patients.Methods Data collected from 170 outpatients visiting the psychiatric clinic at a university hospital. FGIDs were screened according to the Rome III questionnaire-Korean version. Demographic factors were investigated, and psychosocial factors were evaluated using the Hospital Anxiety Depression Scale, Patient Health Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, there was no significant association between age, gender in patients with overlap syndrome. 40 Lee et al 11 found that, in psychiatric patients, the NERD-FD overlap was the most common among NERD, FD, IBS, and functional constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no significant association between age, gender in patients with overlap syndrome. 40 Lee et al 11 found that, in psychiatric patients, the NERD-FD overlap was the most common among NERD, FD, IBS, and functional constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with overlap syndrome also reported more frequent and severe GI symptoms, more severe depressive symptoms, and lower quality of life (QoL) than those with single FGID. 11 In actual clinical practice, overlap FGID can be frequently encountered, and it is important to know the clinical course of overlap FGID because these patients have severe symptoms and are highly likely to be related to psychosocial factors without responding to conservative treatment. However, there have been only few studies on the overlap syndrome 12 - 15 and on follow-up 16 , 17 ; therefore, studies on the characteristics of patients with overlap syndrome and their associated risk factors are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 100.00% (30/30) and 96.67% (29/30) of subjects in the DA-9701 group and placebo group, respectively, also had FD, which was consistent with previous studies showing that many patients with IBS are accompanied by FD. [27][28][29] As a result of efficacy evaluation, there was no statistically significant difference in the proportion of responders with appropriate improvement in overall symptoms of IBS-C. However, the proportion of responders was higher with 53.33% (16/30) in the DA-9701 group than in the placebo group with 40.00% (12/30).…”
Section: Discussionmentioning
confidence: 95%
“…Further, individuals meeting criteria for multiple FGIDs have been shown to suffer both greater gastrointestinal symptom burden 7 and greater psychological symptom burden. [7][8][9] The theoretical conception of gastrointestinal disorders is that symptom clusters defining one gastrointestinal disorder are distinct from another, even among FGIDs. Hence, FD is a distinct syndrome from gastroesophageal reflux disorder (GERD).…”
Section: Introductionmentioning
confidence: 99%